A study on the effectiveness of teaching speaking skill of english as a second language using multiple case studies - Patrick, J.J.D. (University of Jaffna, 2022)
Purpose: The purpose of this study is to find out an effective technique in initiating speaking skill using Multiple Case Studies. Proficiency in speaking English has become a problem in Jaffna. Methodology: In order to solve this problem, the teacher as a researcher devised the qualitative method of longitudinal multiple case studies in real life situation with eight participants. From the research problem, two research questions such as “to what extent authentic interaction in the immediate context does promote communicative proficiency? and what is the effect of using case study in studying speaking skill?” were framed. The answers to the two research questions were found from multiple source of information such as empirical observation of individual case studies, interview and test. Findings: It has been found that students, who performed poorly in the pretest, scored 70 marks in the post test. Even in the delayed post test, same amount of knowledge was retained except in case of one participant. The reason was largely due to his conscious learning of English as a second language grammar as he was highly motivated by the acquisition of speech. When triangulating the results such as tests with participant observation and interview, and analysis of participants showed that speaking skill was the most preferred one, and students were highly motivated to engage in speaking activity. Teaching grammar was not effective. Limitation: The limitation of this study is that it cannot be generalized in a broader context. It is still inconclusive and suggestive that something was going on with regard to the kind of knowledge in speech. In this sense, further research is needed. It supported the Universal theory of Linguistics that everybody has the ability to acquire language, second language, simply being exposure to that language and thereby Findings a solution to the research problem. Implications: It supported the Universal theory of Linguistics that everybody has the ability to acquire language, second language, simply being exposure to that language and thereby Findings a solution to the research problem. The curriculum developers and teachers should take into account this fact. Further, it is true in second language teaching that all four skills have to be covered or included. But the implication of this study is that first of speaking skill should be promotedthrough interaction or initiated in a real life situation, after that equal weight can be given to other skills such as reading and writing. Case study method is very useful to observe naturally as to how learners acquire language without controlling them.
Keywords: Case study; Observation; Proficiency; Test